Think like a forest. Diluting the boundaries between nature and city - Ingersoll, Richard (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2020)
To make the city biomimetic does not mean necessarily to copy nature, but rather to pursue processes analogous to natural ones, diluting the boundaries between nature and cit. Thinking like a forest when approaching urbanism, might lead to sympathize with natural boundaries. The title of this paper reprises a short chapter, “Thinking like a Mountain”, by the great American ecologist Aldo Leopold, published in The Sand County Almanac in 1949. The first part of the paper recall how the relationship between nature and architecture has been understood in the past, quoting some theories, from Abbé Laugier to Christopher Alexander, to Gilles Deleuze, to Peter Wohlleben. In the second part of the paper some reflections are made on a selection of projects that since the 1970s have sought to mitigate the destructive effects of the city on the ecology proposing a closer relationship with nature.
Keywords: Natural boundaries; Urban forestry; Green washing; Biomimetic architecture; Carbon footprint